MATLAB time-based simulations of projectile motion, pendulum oscillation, and water discharge - Yetilmezsoy, Kaan; Mungan, Carl E. (IOP PUBLISHING LTD, 2018)
In addition to teaching undergraduate technical majors about theory and experiments, an important component of their instruction should be to develop proficiency in using computers for simulations and data presentation. A particularly appropriate course for this purpose is classical mechanics because one of the primary goals of that course is to simulate the motion of physical systems, which is greatly aided by visualizations that help to build students' intuition about expected behaviors. As a demonstration of the ease with which this objective can be accomplished using the MATLAB software package, fully executable scripts are presented here for three commonly studied systems: point projectiles, simple pendula, and water flowing out of a hole in a tank. It is much easier for students to edit a functioning script than to try to write their own from scratch. However, the present scripts are sufficiently short and well-documented that instructors can readily ask their students to modify and adapt them according to their local instructional environments and purposes.
Keywords: computational simulation; projectile motion; simple pendulum; water discharge; MATLAB; PHYSICS; COMPUTATION; MECHANICS; EDUCATION; STUDENTS; Education & Educational Research